2013
DOI: 10.1097/aog.0b013e3182a91f45
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four–Month Continuation of Reversible Contraception

Abstract: Objective To estimate 24-month continuation rates of all reversible contraceptive methods for women enrolled in the Contraceptive CHOICE Project. Methods We analyzed 24-month data from the 9,256 participants enrolled in the Contraceptive CHOICE Project, a prospective observational cohort study that provides no-cost contraception to women in the St. Louis region. The project promoted the use of long-acting reversible contraception (LARC; intrauterine devices (IUDs) and implants) in an effort to reduce the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(116 citation statements)
references
References 22 publications
7
103
3
3
Order By: Relevance
“…Smaller inserters may reduce discomfort but it is not likely that these will alter our conclusion of a lack of benefit of ibuprofen. Women choosing an IUD for contraception have the highest continuation and satisfaction rates compared to other contraceptive methods [26]. In recent years, IUD use has risen predominately among parous women [27], and as our study confirmed low pain levels with IUD insertion among parous women, likely no additional pain intervention is necessary for this group.…”
Section: Discussionsupporting
confidence: 61%
“…Smaller inserters may reduce discomfort but it is not likely that these will alter our conclusion of a lack of benefit of ibuprofen. Women choosing an IUD for contraception have the highest continuation and satisfaction rates compared to other contraceptive methods [26]. In recent years, IUD use has risen predominately among parous women [27], and as our study confirmed low pain levels with IUD insertion among parous women, likely no additional pain intervention is necessary for this group.…”
Section: Discussionsupporting
confidence: 61%
“…Age has been shown to impact on implant continuation with younger women having higher rates of discontinuation. 8,14,18 This study found that known removals were less likely for younger women than older women. However, the higher loss to follow up rate of younger women may signal more Jadelle® removals in this group.…”
Section: Discussionmentioning
confidence: 73%
“…Earlier studies have shown Jadelle® continuation rates to be 88-94% at one year. 14,15 A study of women using Norplant® found a 14% discontinuation at two years of use for bleeding problems. 5 At five years, 55% of women were still using the Jadelle® implant, giving a cumulative 5-year life table discontinuation rates for menstrual problems of 16.4/100.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, teens in our cohort continued to use LARC methods longer than short- er-acting methods such as the oral contraceptive pill and DMPA injection; two thirds of teens in CHOICE were still using their LARC method at 24 months of follow-up, as compared with only one third of teens using a non-LARC method. 8 The limitations of our study must be considered. First, information about pregnancy was self-reported by participants, and thus it is possible that the number of teenage pregnancies was underestimated in the CHOICE cohort.…”
Section: Discussionmentioning
confidence: 95%
“…8,9 LARC methods reduce the likelihood of pregnancy and of repeat pregnancy among adolescents, 10,11 yet less than 5% of U.S. teens report using LARC methods. 12 Lack of information about effective contraception, limited access, and cost remain barriers to the use of LARC methods by teens.…”
Section: Long-acting Contr Aception and Teenage Pregnancymentioning
confidence: 99%